Dampak penggunaan e-filling terhadap kepatuhan wajib pajak: peran perilaku wajib pajak sebagai variabel mediasi - Doddy Setiawan; Bobby Kurniawan; Payamta Payamta (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2018)
This research aims at examining the effect of perception of the use of electronic filling (e-filling) on taxpayers’ compliance. Further, the study investigate the role of intention to use as mediating variable on the relation between perception of e-filling and taxpayers’ compliance. Perception of the use of e-filling divide into: perceived usefulness and perceived ease of use. Sample of the study are individual taxpayer with taxpayer registration number. The study conducted at regency at Central Java Province consist of Surakarta, Boyolali, Sukoharjo, Klaten and Karanganyar. The sample of the study consists of 750 taxpayers. The study use SEM analysis to test the hypothesis. The result of the study show that that both perceived usefulness and perceived ease of use have positive effect on taxpayers’ compliance and intention to behave mediate the relationship between perceived usefulness and perceived ease of use on taxpayers’ compliance.